Those girls [large type] - Stevens, Chevy (Thorndike Press, 2015)
"Life has never been easy for the three Campbell sisters. Jess, Courtney, and Dani live on a remote ranch in Western Canada where they work hard and try to stay out of the way of their father's temper. One night, a fight gets out of hand and the sisters are forced to go on the run, only to get caught in an even worse nightmare when their truck breaks down in a small town. As events spiral out of control they find themselves in a horrifying situation and are left with no choice but to change their names and create new lives"--